Characterization of cromolyn sodium hydrates and its formulation by 23Na‐multiquantum and magic‐angle spinning nuclear magnetic resonance spectroscopy. Issue 8 (9th July 2013) - Umino, Makoto; Higashi, Kenjirou; Masu, Hyuma; Limwikrant, Waree; Yamamoto, Keiji; Moribe, Kunikazu
Abstract: We characterized cromolyn sodium (CS) hydrates and evaluated their molecular states in low‐dose formulations using Na‐multiquantum magic‐angle spinning (MQMAS) nuclear magnetic resonance (NMR) analysis. Two CS hydrates, low‐water‐content hydrated form and high‐water‐content hydrated form containing 2–3 and 5–6 hydrates, respectively, were prepared by humidification. Single‐crystal X‐ray diffraction and powder X‐ray diffraction analysis revealed that these CS hydrates contained sodium channel structures and that water molecules were adsorbed on the sodium nucleus. 13 C‐cross‐polarization/MAS NMR spectra of these hydrates revealed similar results, confirming that the water molecules were adsorbed not on the cromolyn skeletons but mainly on the sodium nucleus. In contrast, 23 Na‐MQMAS NMR analysis allowed us to clearly distinguish these hydrates without discernible effects from quadrupolar interaction. Thus, MQMAS NMR analysis is a valuable tool for evaluating salt drugs and their formulations. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:2738–2747, 2013